Modeling and simulation of a batch distillation column for recovering limonene epoxide (2012)
ABSTRACT: Aspen Plus and MATLAB software simulation tools were employed for modeling, simulation and optimization of a distillation process to recover limonene epoxide from a liquid mixture containing limonene + acetonitrile + water + limonene epoxide. This mixture is obtained from limonene epoxidation over PW-Amberlite using aqueous hydrogen peroxide as oxidant and acetonitrile as solvent. Analyses of residue curve maps indicate that batch distillation columns of inverse configuration are adequate to separate limonene epoxide. The model parameters, i.e., the number of stages (8) and the reflux ratio (3,1) were determined by steady state simulations with short-cut models and rigorous models from Aspen Plus. Aspen Plus simulation of the batch distillation operation showed that it is possible to recover up to 95 % limonene epoxide with a molar fraction of 0,97 after 7,5 h. For comparison purposes, the batch distillation operation was also simulated with a semi-rigorous MATLAB model and similar results were obtained.